Toxicants and contraceptives for feral swine in the US - Foster, Justin, speaker; VerCauteren, Kurt, speaker; Eckerly, Doug, speaker; Higginbotham, Billy, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
With partners, we and others are working to develop and register toxicants and contraceptives for feral swine in the US. Our toxicant efforts are focused on using sodium nitrite (SN) as the active ingredient. We are assessing and comparing the palatability, lethality, and general potential of promising formulations of SN in controlled, captive settings. We are also trialing a variety of swine-specific feeders. In this presentation we will provide an update and present our findings to date. We also lay out our path going forward toward the US and Australian registration of a SN-based toxicant for the control of feral swine. In a parallel effort we are also working to develop a species-specific contraceptive reagent for feral swine that can be delivered as a bait and cause permanent sterility. An update on this line of endeavor will also be provided.
Moderator: Billy Higginbotham.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Kurt VanCauteren.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses